Life skills, hopefulness and happiness of college students in the University of the Philippines Diliman - Garcia, Jericho A. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aims to describe the happiness, hopefulness, and life skills of college styudents in the University of the Philippines, Diliman and examine the relationships among these variables. Undergraduate students of the University of the PHilippines, Diliman (n=326) participated in the study. Scores gathered from the participants using these established instruments: the Subjective Hapiness Scale (SHS), the Hunter Opinions and Personal Expectations Scale (HOPES-20), and the Life Skills Assessment Scale (LSAS) were used to measure the individual happiness, hopefulness, and life skills. Results show that in general, the college students have moderate to high levels of hapiness and hopefulness. Students also showed average to high levels of cognitive life skills but displayed low to average levels of emotional life skills. Strong positive correlations among happiness, hopefulness, and life skills were also found. The study recommends strengthening Life Skills education and training of students in the K-12 Home Economics curriculum.